Transformative Paradigms in IT Project Management: A Scholarly Exploration of SAFe® and Azure DevOps Integration for Enhanced Innovation and Strategic Agility (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This scientific investigation presents a groundbreaking exploration of integrating the Scaled Agile Framework® (SAFe®) with Azure DevOps, setting a new benchmark for innovation and strategic agility in IT project management. The study meticulously examines how this fusion optimizes operational efficiency and fosters a culture of continuous improvement and collaboration across diverse project teams. Adopting a multi-metric research approach, it assesses the transformative potential of combining the Agile principles of SAFe® with the robust tools and automation capabilities of Azure DevOps. This synthesis is proposed as a dynamic model for managing complex IT projects where traditional methodologies fail to address the rapid pace of technological advances and market requirements. Key findings highlight the improved flexibility, visibility, and productivity achieved through this integration, highlighting its importance in achieving successful project outcomes. It adds the area of strategic recommendations for IT leaders trying to navigate the challenges of digital transformation, advocating adopting these innovative practices as a cornerstone for future excellence in project management. This work not only contributes to the academic discourse on IT project management but also provides practical insights for practitioners seeking to leverage the latest advances in Agile Methodologies and Azure DevOps practices.